Serious creativity - "De Bono, Edward" (London, 2015)
As competition and the pace of change intensify, companies and individuals need to harness their creativity to stay ahead of the field. Under pressure, people often think they can't be creative; many more are convinced they are not creative at all because they have never been 'arty'. Creative genius Edward de Bono debunks these common notions in this remarkable book. He shows how creativity is a learnable skill - one that everyone can use to improve their performance.
Keywords: Creative thinking